Transcriptome and metabolome analysis reveals PRV XJ delgE/gI/TK protects intracranially infected mice from death by regulating the inflammation - Xu, Lei; Zhang, Yang; Tao, Qian; Xu, Tong; Lee, Feng-qin; Deng, Li-shuang; Jian, Zhijie; Zhao, Jun; Yang, Yanting; Lai, Siyuan; Zhou, Yuan-cheng; Xu, Zhi-wen; et al. (Frontiers in Microbiology, 2024)
Pseudorabies virus can cause inflammation in the central nervous system and neurological symptoms.To further investigate the protective mechanism of PRV XJ delgE/gI/TK in the central nervous system, an intracranial PRV-infection mice model was developed. The results demonstrated that immunization with PRV XJ delgE/gI/TK successfully prevented death caused by PRV-intracranial infection. Subsequently, the brains were collected for transcriptome and metabolome analysis. GO and KEGG enrichment analysis indicated that the differentially expressed genes were primarily enriched in pathways such as TNF, NOD-like receptor, JAK-STAT, MAPK, IL-17 and apoptosis signaling. Metabolomics analysis revealed that the differential metabolites were mainly associated with pathways such as fatty acid degradation, arachidonic acid metabolism, linoleic acid metabolism and unsaturated fatty acid biosynthesis. The combined analysis of metabolites and differentially expressed genes revealed a strong correlation between the differential metabolites and TNF, PI3K, and MAPK signaling pathways. Anti-inflammatory metabolites have been shown to inhibit the inflammatory response and prevent mouse death caused by PRV infection. Notably, when glutathione was injected intracranially and dihydroartemisinin was injected intraperitoneally, complete protection against PRV-induced death in mice was observed. Moreover, PRV activates the PI3K/AKT signaling pathway. In conclusion, our study demonstrates that PRV XJ delgE/gI/TK can protects intracranially infected mice from death by regulating various metabolites with antiinflammatory functions post-immunization.